Magnetic resonance imaging demonstrates gyral abnormalities in Tourette syndrome. Issue 6 (12th July 2022) - McCann, Bernadette; Lam, Melanie Y.; Shiohama, Tadashi; Ijner, Prahar; Takahashi, Emi; Levman, Jacob
Abstract: Tourette syndrome (TS) is a neurological disorder characterized by involuntary and repetitive movements known as tics. A retrospective analysis of magnetic resonance imaging (MRI) scans from 39 children and adolescents with TS was performed and subsequently compared with MRI scans from 834 neurotypical controls. The purpose of this study was to identify any differences in the regions of motor circuitry in TS to further our understanding of their disturbances in motor control (i.e., motor tics). Measures of volume, cortical thickness, surface area, and surface curvature for specific motor regions were derived from each MRI scan. The results revealed increased surface curvature in the opercular part of the inferior frontal gyrus and the triangular part of the inferior frontal gyrus in the TS group compared with the neurotypical control group. These novel findings offer some of the first evidence for surface curvature differences in motor circuitry regions in TS, which may be associated with known motor and vocal tics. Abstract : A retrospective analysis of magnetic resonance imaging (MRI) scans from 39 children and adolescents with Tourette syndrome (TS) was performed and subsequently compared with MRI scans from 834 neurotypical controls. Results revealed increased surface curvature in the opercular and triangular parts of the inferior frontal gyrus in TS. These findings offer evidence for surface curvature differences in motor circuitry regions in TS, which may be associated with known motor and vocal tics.